Factors associated with delivering premature and/or low birth weight infants among pregnant HIV-positive women on antiretroviral treatment at Dr George Mukhari Hospital, South Africa. Issue 2 (3rd April 2018) - Gibango, NN; Mda, S; Ntuli, TS
Abstract: Background: Prematurity and low birthweight (LBW) deliveries amongst pregnant women infected with the human immunodeficiency virus (HIV) remain a challenge worldwide. The association between prematurity, LBW and antiretroviral therapy (ART) or prophylactic antiretroviral drug (ARV) exposure in pregnancy is unclear. This study evaluates the risk of delivering a premature and/or LBW infant among HIV-positive pregnant women on ART or prophylactic ARV. Methods: A cross-sectional study was conducted (April to October 2012). HIV-positive women on prophylactic ARV (dual therapy) or lifelong ART (triple therapy or HAART) were enrolled in the study. Women who did not have a documented HIV result during pregnancy, those tested before delivery and those found to be HIV-positive were considered as not exposed to ARV drugs during pregnancy. This group received a standard dose of nevirapine during labour. The control group was made up of HIV-negative women. Results: Of the 496 mothers enrolled in the study, 59% (288/496) were HIV-positive, of whom 72% (206/288) were on ART or prophylactic ARV. The mean age was 27.6 ± 6.5 years (15 to 47 years). The mean gestational age (GA) was 35.9 ± 3.6 weeks (24–42 weeks). Infants' birthweights ranged from 550 to 4 900 g (2.5 ± 0.9 kg). HIV-positive mothers not on ART or ARV prophylaxis were likely to deliver an infant at GA < 28 weeks ( p < 0.05) or birthweight < 1 000 g ( p < 0.05) compared with their counterparts. Conclusion: HIV-positive pregnant women not on ART or ARV prophylaxis were at a risk of delivering babies at GA < 28 weeks or birthweight < 1 000 g. There is a need to encourage early and regular attendance for antenatal care so that HIV-positive pregnant women can be identified and have access to treatment during pregnancy.